Extending the “Reach” of the Short-Scar Facelift with Energy Devices—An Early Report - Fedok, Fred G. (Facial Plastic Surgery, 2021)
Facial rejuvenation has become more popular. A wider breadth of the patient population is seeking procedures to preserve their youthful facial attributes and to remedy age-related deleterious changes. Along with this increasing interest in facial rejuvenation is also the expressed desire for any interventions to be relatively low risk, with limited recovery, and with achievable positive results. Many new technologies have become available in an attempt to improve age-related facial changes. The radiofrequency (RF)-based technologies are largely directed toward skin tightening and toward reducing and remodeling subcutaneous fat. It can be contemplated that the combination of RF-based technology with limited surgical procedures may extend the patient selection for less invasive procedures while improving potential results. This is a report of the combination of radiofrequency technologies—percutaneous and transcutaneous—with short scar face techniques in facial rejuvenation.
Keywords: radiofrequency; facelift; minimally invasive; facial rejuvenation; MACS lift; short scar